Professional development training of cadets at military universities - Alexey A. Pichkurov (Известия Саратовского университета. Новая серия. Серия Акмеология образования: Психология развития, 2021)
The research appears to be of relevance due to the ongoing modernization of the system of military training. One of its directions is to establish the compatibility of personal and professional qualities of cadets with the model of a modern military specialist. The aim of the research is to carry out a qualitative analysis of the requirements imposed on the modern military by society and the state in order to reveal the essence of the professional development training of cadets. The study hypothesizes that the collective and co-operational nature of professional development training implemented on the basis of a culturological approach to education creates optimal conditions for the professional and personal growth of cadets in the process of their introduction to military culture. The difference between professional training and military training is analyzed. The culturological approach to cadet professional development training is justified as the methodological basis of professional development training. The author proposes an axiological interpretation of the process of professional development training within the framework of the culturological approach. The main aspects of professional development training are briefly described: intellectual, moral, physical, labor. The key principles of professional development training based on the culturological approach are identified: purposefulness, consistency, continuity, professional orientation, patriotic orientation, humanism, and collectivism. The article emphasizes the collective and co-operational nature (polysubjectivity) of professional development training. The author suggests the definition of the “subject of professional development training”. The subjects of professional development training are cadets, officers, teachers, and university cultural organizations. Apparently, the structure of professional development training (its organizational, content and procedural aspects) varies depending on the subject of professional development training. The article concludes that introduction of practices of psychological and pedagogical support of the prospective military into their professional development training can be seen as the way to modernize the system of professional development training at military universities.